The Application of Good Corporate Governance for the Minority Shareholders' Rights: A Literature Review - Delviana Julia; Revina Setiawan; Vincent Haryanto; Willy Willy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study uses the Systematic Literature Review (SLR) method to identify and synthesize findings from various studies related to Good Corporate Governance (GCG) and the protection of minority shareholders. From the eight main articles analyzed, it was found that the principles of fairness, information transparency, and supervision by corporate bodies, particularly independent commissioners, play a significant role in preventing abuse of authority. However, the effectiveness of such protection is highly dependent on the quality of GCG implementation in companies and the consistency of regulators in enforcing the rules. The results of the study confirm that strong implementation of GCG not only increases the confidence of minority investors, but also creates more balanced and ethical corporate governance.